Welfare Traps in Australia: Do they Bite? - Dockery, A.M.; Wood, G; Ong, R (My University, 2008)
Minimising disincentives to employment participation that arise as a consequence of providing welfare has been a major objective of the recent welfare reform agenda in Australia. Of particular concern have been the high effective marginal tax rates (EMTRs) and replacement rates (RRs) facing welfare recipients as a result of the interaction of the tax and benefits system. Based on the financial-year income data contained in waves 1 to 4 of the Household, Income and Labour Dynamics in Australia Survey, the first part of this paper presents estimates of EMTRs facing all working-age Australians and of an alternative ‘disincentive’ measure, participation tax rates (PTRs), for non-working Australians. Significant innovations in the calculation of these measures are the incorporation of the effect of the withdrawal of rental subsidies for public housing tenants, which have not been included in the previous literature, and the allowance for changes in tax liabilities and benefit entitlements for the income unit rather than just for the individual. We find EMTRs and PTRs to have changed very little between 2000-01 and 2003-04, and to be particularly high for recipients of NewStart Allowance. In the second part of the paper we estimate the impact of EMTRs, the PTR and the more commonly used RR on the probability of transitions from non-employment to employment one year later. The PTR and RR are found to be superior to the EMTR in measuring disincentive effects for non-working persons. Second, these effects do matter. High PTRs or RRs have a moderate but significant effect on the probability that women will enter employment from outside the labour force, and a very large (negative) effect on the probability that an unemployed person will find work.
CLMR Discussion Paper Series
Keywords: Benefits and Payments; Employment; Employment -- Incentives; Labour market; Benefits and Payments; Employment; Incentives; Employment and unemployment